2020
DOI: 10.1108/jima-02-2020-0051
|View full text |Cite
|
Sign up to set email alerts
|

The application of the theory of reasoned action on services of Islamic rural banks in Indonesia

Abstract: Purpose The Islamic rural banks have the potential to grow in Indonesia. It is important to learn and study the consumer behaviors toward the Islamic rural banks’ services to plan for future strategies. The purpose of this paper is to test the applicability of the theory of reasoned action in predicting the customers’ decision to use the Islamic rural banks’ services. Design/methodology/approach The descriptive and structural equation model analyses were used to analyze the data. A random sampling technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 98 publications
5
26
1
3
Order By: Relevance
“…Purchase intention refers to an individual's readiness and willingness to purchase a particular product or service (Ajzen, 2015b(Ajzen, , 2015c(Ajzen, , 2020, and it can influence consumer purchasing decisions in the future. These results are consistent with the research of Bashir et al (2019) and Effendi et al (2020) which proves that interest is a reliable predictor of behavior in purchasing behavior of halal products…”
Section: The Influence Of Purchase Intention For Halal Food Products supporting
confidence: 93%
“…Purchase intention refers to an individual's readiness and willingness to purchase a particular product or service (Ajzen, 2015b(Ajzen, , 2015c(Ajzen, , 2020, and it can influence consumer purchasing decisions in the future. These results are consistent with the research of Bashir et al (2019) and Effendi et al (2020) which proves that interest is a reliable predictor of behavior in purchasing behavior of halal products…”
Section: The Influence Of Purchase Intention For Halal Food Products supporting
confidence: 93%
“… Effendi et al. (2020) revealed that the variables of compliance, promotion, service, attitude, subjective norms, and intention have a significant effect on Islamic BPR services.…”
Section: Existing Researchmentioning
confidence: 99%
“…Based on the explanation of the research results above, there are several lessons that we can take. First, the application of the marketing concept to IMFI has been proven to increase customer loyalty ( Effendi et al., 2020 ). Second, customers still make service costs a significant factor in choosing financial products ( Rokhman and Abduh, 2019 ).…”
Section: Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latest 2018 report the vast majority of entrepreneurs were in these categories with 3,667,873 (99.3%) out of the total 3,694,195 entrepreneurs (Widarjono et al, 2021). The IRB had provided loans of up to 10.6 trillion rupiahs or 28.3% of the total Islamic microfinance financing to support the small and medium enterprises (Effendi et al, 2021;Financial Services Authority, 2020;Shaban et al, 2014). In addition, the growth of the Financing to Deposit Ratio (FDR) in IRB was rapid and has reached 119.72%, a significant reinforcement indeed for small and medium enterprises in Indonesia (Financial Services Authority, 2020;Muhammad et al, 2020;Priyadi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%